Comprehensible Input and Krashen's theory. Issue 39 (2019) - Patrick, Robert
Abstract : Over the last 20 years in the United States a curious and likely unpredictable movement has been evolving in the way that we teach Latin and ancient Greek. A set of pedagogical principles known as Comprehensible Input (hereafter CI) has become a vehicle of change affecting our classrooms, our professional organisations and our teacher training programs as well as our relationships with and our positions in world language organisations. These changes to the teaching of classical languages were unpredictable because at the outset CI represented a set of hypotheses and then principles that even their progenitor, Stephen Krashen, thought of as the way into acquiring modern languages while teachers of classical languages had constructed a fortified wall around themselves built on the notion that Latin and ancient Greek were uniquely different from modern languages and, therefore, required different approaches. In many iterations of this wall, only a select cadre of students was thought (and easily demonstrated to be) capable of or even interested in mastering classical languages. This article will examine very briefly what this wave of change has been like in the Latin classrooms and institutions of the US and examine in particular the principles of Comprehensible Input: what they propose, how they are being practised in Latin classrooms, and the obstacles they encounter as well as opportunities they afford Latin programs which intend to survive and thrive in the coming years.